Bank's Capital Legal Procedures to UMKM by Banking Laws in Indonesia - Sudarmanto, HeriLilik (International Journal of Economics and Financial Modelling, 2019)
The purpose of this paper is to describe the legal procedures that must be met by Micro, Small and Medium Enterprises (MSMEs) and a solution (win solution) so that MSMEs can obtain loan capital from banks even though the requirements are incomplete. This study uses a qualitative method by finding a literature review that is truly appropriate to answer the purpose of the problem in this paper. The findings reveal that there are procedures that must be adhered to by both parties as a form of adherence to Positive Laws and Indonesian Government Regulations. The Bank can provide permodalah access to MSMEs without collateral with a maximum loan limit and certain conditions such as the existence of an MSMEs financing guarantor institution in accordance with a mutual agreement between the MSMEs, the guarantor institution, and the Bank as the creditor. MSMEs can also obtain capital loans provided that these businesses implement good business governance. Like making clear financial statements. This is very important, because based on the search results and findings of researchers, banks provide an assessment of MSMEs based on five criteria, namely Character, Capital, Capacity, Condition, and Colleteral.